Serological and histopathological study of thyroid diseases, prospective study - Mohamed, Mohammad Jasim (AL-Kindy College Medical Journal, 2014)
Background: Accurate detection of thyroid autoantibodies by enzyme linked immunosorbant assay technique namely thyroglobulin antibody, thyroid peroxides antibody is crucial in the differentiation of autoimmune thyroid disorders from other form of thyroid diseases.Objective: Evaluation of the detection of thyroglobulin antibody and thyroid peroxides antibody in different thyroid diseases using enzyme linked immunosorbant assay technique.Methods: - Seventy-five patients admitted to Surgical Units of Baghdad Medical City Hospital for the period between "October 2010 to June 2011" they were waiting to do thyroidectomy. They were chosen nonselectively for serological evaluation of above autoantibodies , and correlation of the results with histopathological diagnosis.Results:- Clinical results; Colloid goiter is common cause of hyperthyroidism (19 were colloid goiter out of 30 total hyperthyroid patients ) (63%) , and still common thyroid surgery (56 were colloid goiter out of 75 thyroid surgery) (75%).Histopathological results;- 56 cases (75%) had colloid goiter, 9 patients had Graves' disease (12%), and 3 had lymphocytic thyroiditis (4%), 7 had thyroid neoplasia (both benign and malignant) (9%).The serological results; Antibodies positive results were 6 patients (10.7%) in colloid goiter ( p-> 0.05), 6 patients (66%) and 1 patient (33%) for GD, and lymphocytic thyroiditis respectively( P-< 0.05)., while its all were negative in thyroid neoplasia.Conclusion:- Serum thyroid autoantibodies determination is valuable test in clinical practice of autoimmune thyroid diseases.